Micro- and nano-patterned conductive graphene-PEG hybrid scaffolds for cardiac tissue engineering - Smith, Alec S. T.; Yoo, Hyok; Yi, Hyunjung; Ahn, Eun Hyun; Lee, Justin H.; Shao, Guozheng; Nagornyak, Ekaterina; Laflamme, Michael A.; Murry, Charles E.; Kim, Deok-Ho (ROYAL SOC CHEMISTRY, 2017)
A lack of electrical conductivity and structural organization in currently available biomaterial scaffolds limits their utility for generating physiologically representative models of functional cardiac tissue. Here we report on the development of scalable, graphene-functionalized topographies with anisotropic electrical conductivity for engineering the structural and functional phenotypes of macroscopic cardiac tissue constructs. Guided by anisotropic electroconductive and topographic cues, the tissue constructs displayed structural property enhancement in myofibrils and sarcomeres, and exhibited significant increases in the expression of cell-cell coupling and calcium handling proteins, as well as in action potential duration and peak calcium release.
Keywords: CARDIOMYOCYTES; CONSTRUCTS; MUSCLE